EVOLUSI KONGLOMERASI DI JEPANG: TRANSISI DARI ZAIBATSU KE KEIRETSU DAN IMPLIKASINYA TERHADAP KEBIJAKAN EKONOMI PASCA-PERANG DUNIA II - Muhammad Badar Anugrah Illahi; Imam Mahdi (Dinamika Global)
This study examines the economic transition in Japan from Zaibatsu to Keiretsu post-World War II and its impact on economic policies. Although Zaibatsu was dissolved by the American occupation, the conglomerate structure persisted in the form of Keiretsu, linking companies through cross-shareholding with banks at the core. This research uses a qualitative approach to explore the implications of this transition on Japan's economic policies, based on the International Political Economy (IPE) and Neoliberalism theories. Keiretsu plays a crucial role in maintaining Japan's economic stability, though challenges such as reduced market competition and entrenched management remain. The study concludes that Keiretsu remains relevant despite the pressures of globalization.